72.7k views
1 vote
3 1/4 - 3 1/6 uhmmm yeahh

1 Answer

6 votes

Given the Subtraction:


3(1)/(4)-3(1)/(6)

You can identify that the denominators are different, then, you need to follow these steps in order to find the Difference (the result of the Subtraction):

1. Find the Least Common Denominator (LCD):

- Decompose the denominators into their Prime Factors:


\begin{gathered} 4=2\cdot2=2^2 \\ 6=2\cdot3 \end{gathered}

- Multiply the common and non-common factors with the largest exponents:


LCD=2^2\cdot3=12

2. Divide the LCD by each original denominator and multiply the Quotient by the corresponding numerator:


\begin{gathered} =3(1\cdot3)/(12)-3(1\cdot2)/(12) \\ \\ =3(3)/(12)-3(2)/(12) \end{gathered}

3. Subtract the whole number parts and then subtract the fractions. You get:


\begin{gathered} =0(3-2)/(12) \\ \\ =(1)/(12) \end{gathered}

Hence, the answer is:


=(1)/(12)

User Virgile
by
8.6k points

Related questions

asked Nov 2, 2024 43.6k views
Casper Nybroe asked Nov 2, 2024
by Casper Nybroe
8.4k points
1 answer
1 vote
43.6k views
asked Feb 23, 2024 192k views
Florian asked Feb 23, 2024
by Florian
7.5k points
1 answer
5 votes
192k views
asked Nov 1, 2021 78.9k views
Kiradotee asked Nov 1, 2021
by Kiradotee
8.3k points
2 answers
4 votes
78.9k views